Implementation of the AHP Method in Determining the Completion of Logistics Warehouse Stock Buildup Using the Expert Choice Application: Implementasi Metode AHP dalam Menentukan Penyelesaian Penumpukan Stok Gudang Logistik Menggunakan Aplikasi Expert Choice - Afifah, Sofie Amalia; Cahyana, Atikha Sidhi (Universitas Muhammadiyah Sidoarjo, 2024)
The development of logistics services that are increasing has caused an increase in customers of PT. Astrans Putra Logistik also increased, this resulted in the logistics warehouse capacity experiencing a buildup of goods that almost filled the warehouse capacity which made operational activities disrupted, and many complaints from customers. Resolution to overcome this warehouse problem needs to be done so that the company’s operational efficiency is not disrupted and warehouse stock capacity becomes better. This study aims to find out the best solution of warehouse problems that occur through a decision making support system design using the AHP method assisted by the use of the Expert Choice 11 application. In making this decision, 4 stages are carried out, namely Intelligence, Design, Choice, and Analysis of Assessment Result which in the process have a 4 kinds of criteria and 4 kinds of alternative solutions. From the calculation of the AHP method assisted by the use of the Expert Choice 11 application, the weight of each criterion was obtained, namely Increased Operational Efficiency getting a weight of 0,259, Number of Items that can be Accommodated getting a weight of 0,086, Company Income getting a weight of 0,495, and Company Expense getting a weight of 0,160. From the calculation of alternative settlements, it was also found that The Addition of a New Departure Fleet got a weight of 0,385, The Construction of Branch Goods Warehouse got a weight of 0,279, Upgrading Small Trucks to Large Trucks got a weight of 0,187, and The Application of a Pre-order system for customers got a weight of 0,149.